PENGARUH KOMPENSASI, KEPEMILIKAN MANAJERIAL, DIVERSIFIKASI PERUSAHAAN DAN UKURAN KAP TERHADAP MANAJEMEN LABA - Satria Nugroho; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the effect of compensation, managerial ownerships, corporate diversification, and auditor size to earnings management. Earnings management is measured using the discretionary accruals. Independent variables used in this study is compensated board of commissioners and board of directors, managerial ownerships, corporate diversification, and auditor size while the dependent variable is earnings management. Several previous studies have shown varying results. To obtain valid results, the testing performed on each variable based on the hypothesis constructed. The study population was 114 manufacturing companies listed in Indonesia Stock Exchange. The samples used were selected by purposive sampling method. After reduction with several criteria, 38 companies are identified as samples. Observation period is 2011-2013 years, so the number of samples used is 114 samples. Hypothesis testing is performed by using the Regression Analysis The result of this study showed that managerial ownerships and corporate diversification has significant effect on earnings management, while compensation and auditor size has no significant on earnings management.